Skrining Fitokimia dan Aktivitas Antibakteri dari Daun Bamban (Donax canniformis) untuk Formulasi Obat dari Bahan Alam (Phytochemical Screening and Antibacterial Activity of Donax canniformis for The Formulation Medicine from Natural Ingredients) - ihsan, Hamlan Hamlan (Kementerian Perindustrian, 2017)
Bamban (Donax canniformis) is a plant of the Marantaceae family that has many uses, among others, as a craft and traditional medicine in South Kalimantan. The young leaves were used to treat eyes irritation by local people in South Kalimantan. This study aims to determine the chemical compound in young and mature bamban leaves and evaluate their antibacterial and antiradical activity. The young and mature bamban leaves were extracted separately by maceration technique using 80% ethanol. The liquid extract were filtered and then concentrated with a vacuum oven at 45Â°C. The flavonoid compound were detected using HPLC using quercetin, rutin and catechin standard. Antibacterial activity was tested using agar well diffusion method and radical scavenging activity using DPPH method. Results showed the yield of mature and young leaves were 1.50% and 0.71%. Both extracts contained rutin and catechins. None of quercetin was detected in both extracts.The young leaves extract inhibited Salmonella, E.coli, and P.aeruginosa bacteria at 15% concentration of extract. The mature and young leaves extract had radical scavenging activity at 45.34% and 18.50% respectively.Keywords : antibacterial, bamban leaves, DPPH, ethanol, flavonoid